Diabetes Management in Patients With Dementia: A Quality Improvement Project to Enhance Staff Confidence, Understanding, and Patient Care - Vipassana Bajracharya; Hugh Kelly; Vatsala Mishra; Latha John; Stacey Blackford (BJPsych Open, 2025)
Aims: This quality improvement project (QIP) aimed to improve nursing staff confidence and understanding of diabetes/management by 40% by the end of February 2024, taking place on a dementia intensive care ward in South East London. This project was led by a medical student and FY2 doctor who noticed significant anxiety and uncertainty amongst healthcare professionals (HCPs) managing a patient’s severe type-2 diabetes, leading to disruption in care as HCPS sought repeated consultation with medics for reassurance prior to implementation of plans, creating an environment of dependency and reduced confidence making independent decisions. Barriers to delivering high-quality care for diabetes in psychiatric services are well-documented and associated with limited understanding of the condition and low confidence in management. Suboptimal management increases risk of diabetic emergencies such as diabetic ketoacidosis/Hyperosmolar Hyperglycaemic State (DKA/HHS), and long-term complications.